The Relationship Between the Coverage of Antenatal Care (K4) Visits to Flood Incidents - Kholifatul Ummah (EMBRIO: Jurnal Kebidanan, 2024)
Antenatal care or pregnancy care/examination is one of the factors that is very important to be considered and carried out by pregnant women to prevent complications until death occurs during childbirth, in addition to that, it is also very important to maintain and monitor the health and growth of the fetus. The main problem that is the highest is the maternal and infant mortality rate. The KIA program is responsible for providing health services to pregnant women, mothers giving birth, and neonatal babies. Floods are a form of disaster in Indonesia that occurs almost every year. In the last ten years, flood disasters have always occupied the first position of disaster events. Ngrame Village is one of the villages in the Pungging Mojokerto sub-district that experienced a flood event. The flood incident was caused by the collapse of barriers in two rivers in the Mojosari Region, and 4 points broke. The initial survey results in March 2024 showed that ten pregnant women in TM III and 20 pregnant women in TM III were evacuated to other villages due to the flood disaster in Ngrame village. Using the chi-square test, this study uses the cross-sectional method located in Polindes, Ngrame Village, with a sample of 20 TM III pregnant women. The results of the calculation of the chi-square test using SPSS (value = 0.00) can be concluded so that it can be concluded that Ho was accepted as having a relationship between the coverage of antenatal care (K4) visits to flood events in Polindes, Ngrame Village, Watukenongo Health Center, Mojokerto Regency.